Hubungan Antara Ibu Hamil Usia Muda Dengan Anemia Di Bpm â€œTâ€ Cikutra Kota Bandung - Haidir Syafrullah; Yasmin Widad Chabellalia (Sehat MasadaJurnal, 2019)
Pregnancy at too young maternal age is a pregnancy in adolescents under 20 years of age who are not ready enough to get pregnant. Risk factors that may occur are miscarriage, premature delivery, low birth weight, congenital abnormalities, easy to contract the infection, anemia in pregnancy, and death. Adolescence is also a risky time to get pregnant. This study aims to determine the relation between a young age pregnant women with anemia at BPM â€œTâ€ Cikutra, Bandung 2015. The research methodology used in this study is the correlation obtained from secondary data in the medical record book ANC in 2015 with bivariate techniques. Samples technique used in the study a total of sampling as many as 64 people. The results showed the majority of pregnant women (56.25%) are in the middle of adolescence (15-18 years old). The majority of pregnant women (51.56%) had moderate anemia. There is a relation between middle adolescence with moderate anemia (61.11%) with a p-value (0.003). As a suggestion, health promotion is expected to be held on the age of the mother at risk for pregnant and carry out safe motherhood to reduce 4 overly conditions (overly young, overly aged, overly close, and overly often get pregnant). Hopefully health providers can inform reproductive health to adolescents and the elderly.